Solar pyrolysis of waste rubber tires using photoactive catalysts. (July 2018) - Hijazi, Ayman; Boyadjian, Cassia; Ahmad, Mohammad N.; Zeaiter, Joseph
Highlights: TiO2 based photocatalysts were applied in the solar pyrolysis of waste rubber. Pt, Pd and Bi2 O3 /SiO2 doping enhanced the TiO2 cracking ability. The highest gas yield of 41% was achieved over Pd/TiO2 . The lowest carbon number of the pyrolysis oil was achieved over Pd/TiO2 . Abstract: The solar pyrolysis of waste tire rubber was investigated with the application of heterogeneous photocatalysts including TiO2, Pd/TiO2, Pt/TiO2, Pd-Pt/TiO2, and Bi2 O3 /SiO2 /TiO2 . Experiments were performed at temperatures ranging between 550 and 570 °C under solar irradiations of 950–1050 W/m 2 . The gas yield from non-catalytic solar pyrolysis was at 20% while the use of TiO2 catalyst increased the gas yield to 27%. Doping of TiO2 with noble metals and Bi2 O3 /SiO2 metal oxides enhanced further the cracking ability of the catalyst. Bi2 O3 /SiO2 /TiO2 gave a 32% gas yield. The highest gas yields of 40% and 41% were achieved over Pd-Pt/TiO2 and Pd/TiO2 catalysts, respectively. Catalyst characterization by BET, SEM, EDX and XRD showed the role of metal doping in altering the morphology of TiO2, resulting in nanocrystallites, larger pore volume and higher surface area. Both, Pd and Bi influenced the photocatalytic properties of TiO2 improving cracking activity during pyrolysis of waste rubber.